Augmented Reality Technology for Learning Introduction Media of Various Vegetables Android Based using Unity - Agustinus Sirumapea; Syaipul Ramdhan; Ferawati Ferawati; Rio Nurrizkiyadi (JURNAL SISFOTEK GLOBAL, 2022)
Technological developments are getting faster over time in all fields and in various sectors, one of the fast developments is gadgets. This affects people at various ages who make gadgets as a medium of information and also learning media for children. Early childhood is the most important period in human life. This is because at an early age children are sensitive to receiving external stimuli, so that children must be given educational stimuli to help physical and spiritual growth and development so that children have readiness to enter education at a further level. The application of Augmented Reality for learning media for the introduction of various vegetables aims to make it easier for Kindergarten and PAUD teachers to deliver learning materials for the introduction of various vegetables to children and is also more interactive because there is additional media for Augmented Reality marker cards that can be scanned with a camera. smartphone and take out a 3D object from the shape of a real vegetable. In this application, there are also practice questions that can be done to train children's memory after getting to know 10 kinds of vegetables. This application can be used on smartphones with the Android operating system.